Research within Evaluation: the case of Northern Ireland In K.Bush and C. Duggan (eds) Evaluation in the Extreme: Research Impact and Politics in Violently Divided Societies - Knox, Colin (My University, 2015)
This chapter looks at the evaluation of research within programme evaluation under four key headings:  The evaluation of research on the theory of change which provides the rationale for the programme.  An evaluation of the research conducted by the delivery agents to assess the formative impact of the programme aimed at checking programme delivery.  The role played by the evaluator in assessing research within the context of programme evaluation.  The influence of research as one component in a programme of activities, and the contribution it makes to the overall programme objectives.
Keywords: Northern Ireland